Eosinophils and cytokines in mild asthma and allergen-induced asthma - Woolley, Karen L. (My University, 1993)
Asthma is a chronic respiratory disease, characterized by variable airflow obstruction, airway hyperresponsiveness and airway inflammation. Prior to starting this thesis, information on the role of inflammatory cells and cytokines in asthma was limited. The aim of this thesis was to determine the roles of eosinophils, an inflammatory cell believed to be important in asthma, and GM-CSF and IL-3, cytokines shown to regulate eosinophils in vitro, in mild and allergen-induced asthma. Fiberoptic bronchoscopy was performed on each subject and blood, bronchoalveolar lavage and bronchial biopsy samples were obtained. In comparison to non-asthmatics, eosinophil number and activity and GM-CSF levels were increased in asthmatics. GM-CSF levels correlated with eosinophil number and activity and airway responsiveness correlated with eosinophil number and activity and GM-CSF levels. IL-3 was detected in both asthmatics and non-asthmatics, with no difference apparent between the groups. These findings indicate that eosinophils, potentially regulated in vivo by GM-CSF, contribute to airway inflammation in mild asthma. In comparison to the control diluent inhalation, allergen inhalation caused increases in eosinophil number and activity and GM-CSF levels. IL-3 levels did not change after allergen. Eosinophil number and activity correlated with GM-CSF and the severity of the late asthmatic response correlated with the number and activity of eosinophils. These findings indicate that an increase in eosinophil number and activity, possibly due to GM-CSF, contributes to allergen-induced asthma. This thesis has demonstrated cellular and cytokine involvement in mild and allergen-induced asthma. For the first time, the presence of GM-CSF and IL-3 cytokines, at the protein level, have been demonstrated in the airways of subjects with mild and allergen-induced asthma. Eosinophils, potentially regulated by GM-CSF, appear to play an important role in the disordered airway function associated with asthma.
Keywords: Pharmacology; Physiology; Pharmacology